Pemodelan Perilaku Tegangan Dan Regangan Beton Saat Terbakar - Rahmadhan, Wahyu; Kamaldi, Alfian; Suryanita, Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Concrete exposed to high temperatures decrease its strength. Droped down in concrete strength under strength requirement will make the concrete fail to be functioned. The strength of the concrete can be determined from laboratory test, or mathematic model based on the results from experimental test. This study aims to identify the behavior of the stress and strain of the concrete exposed to high temperatures. The model was carried at using Finite Element Software LUSAS and the results compared to mathematic model proposed by Li and Purkiss (2005) and Chang (2006). The speciment used in this study was cylindrical with diameter of 150 mm and height of 300 mm with a 25 MPa of the concrete strength. The model was simulated burning with a constant temperature that varied from 100°C to 800°C. The result showed that strain stress curve shown from the empirical formula has an elastic phase of 0.6f'c, while modeling based LUSAS has an elasticity phase of 0.45 f'c. The difference between the elastic and plastic phases in the LUSAS model was clearly visible according to the temperature of the concrete, while the models using the empirical formula were not affected by temperature. It can concluded that empirical formula model and LUSAS can be used as a reference for the behavior of concrete when exposed to high temperatures.Keywords : modeling, high temperature, stress, strain, LUSAS